2017
DOI: 10.3847/2041-8213/aa9060
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the First Electromagnetic Counterpart to a Gravitational-wave Source by the TOROS Collaboration

Abstract: We present the results of prompt optical follow-up of the electromagnetic counterpart of the gravitational-wave event GW170817 by the Transient Optical Robotic Observatory of the South Collaboration. We detected highly significant dimming in the light curves of the counterpart (g 0.17 0.03 D =  mag, r 0.14 0.02 D =  mag, i 0.10 0.03 D =  mag) over the course of only 80 minutes of observations obtained ∼35 hr after the trigger with the T80-South telescope. A second epoch of observations, obtained ∼59 hr afte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 22 publications
3
63
0
Order By: Relevance
“…This multimessenger data provided convincing answers to many outstanding questions. For instance, the detection of a short gamma ray burst (GRB) 1.7 seconds after GW170817 [24][25][26], and subsequent kilonova [27][28][29][30][31][36][37][38][39][40][41][42][43][44], confirmed that BNS mergers are a progenitor of these events. Lanthanide signatures in the kilonova light curves also showed BNS mergers to be a major site for nucleosynthesis of elements heavier than iron [40,44,47,48].…”
Section: Introductionmentioning
confidence: 78%
“…This multimessenger data provided convincing answers to many outstanding questions. For instance, the detection of a short gamma ray burst (GRB) 1.7 seconds after GW170817 [24][25][26], and subsequent kilonova [27][28][29][30][31][36][37][38][39][40][41][42][43][44], confirmed that BNS mergers are a progenitor of these events. Lanthanide signatures in the kilonova light curves also showed BNS mergers to be a major site for nucleosynthesis of elements heavier than iron [40,44,47,48].…”
Section: Introductionmentioning
confidence: 78%
“…As one of the best sGRB events observed ever, GW170817 is rich in new data; E-mail: hamidani.hamid@yukawa.kyoto-u.ac.jp such as, the mass of the BNS (∼ 2.7M ; Abbott et al 2017a), the viewing angle (∼ 20 • − 30 • ; Abbott et al 2017a;Troja et al 2018), and the delay between the GW and the EM signal (∼ 1.7s; Abbott et al 2017a;Abbott et al 2017c), all inferred for the first time. Superluminal motion in late radio afterglow observations (Mooley et al 2018), and macronova/kilonova (hereafter macronova) emission with a strong support for r-process nucleosynthesis (Arcavi et al 2017;Chornock et al 2017;Coulter et al 2017;Díaz et al 2017;Drout et al 2017;Kilpatrick et al 2017;Kasliwal et al 2017;Nicholl et al 2017;Pian et al 2017;Smartt et al 2017;Shappee et al 2017;Soares-Santos et al 2017;Tanaka et al 2017;Utsumi et al 2017;Valenti et al 2017) are also new revelations. This event also had impacts on the equation of state of neutron stars, relativity, cosmology, etc.…”
Section: Introductionmentioning
confidence: 93%
“…The simultaneous detection of gravitational waves (GWs) from a neutron star-neutron star (NS-NS) merger (Abbott et al 2017a) and its electromagnetic (EM) counterparts opened a new window of the multimessenger astronomy. EM counterparts to GW170817 were observed over the entire wavelength range, from gamma-ray to radio wavelengths (Abbott et al 2017b;Andreoni et al 2017;Arcavi et al 2017;Coulter et al 2017;Cowperthwaite et al 2017;Díaz et al 2017;Drout et al 2017;Evans et al 2017;Hu et al 2017;Valenti et al 2017;Kasliwal et al 2017;Lipunov et al 2017;Pian et al 2017;Pozanenko et al 2018;Smartt et al 2017;Tanvir et al 2017;Troja et al 2017;Utsumi et al 2017;Mooley et al 2018;Hallinan et al 2017). In particular, a counterpart in optical and infrared wavelengths (named as SSS17a, AT 2017gfo or DLT17ck), is identified as the emission so-called a kilonova (also known as macronova).…”
Section: Introductionmentioning
confidence: 99%